Bridging Reading Aloud and Speech Production - Simone Sulpizio (Frontiers Research Topics, 2016)
For decades, human cognition involved in reading aloud and speech production has been investigated extensively (a quote search of the two in google scholar produces about 83,000 and 255,000 results, respectively). This large amount of research has produced quite detailed descriptions of the cognitive mechanisms that allow people to speak or to read aloud a word. However, despite the fact that reading aloud and speech production share some processes - generation of phonology and preparation of a motor speech response - the research in this two areas seems to have taken parallel and independent tracks, with almost no contact between the two. The present Research Topic takes an initial step towards building a bridge that will link the two research areas, as we believe that such an endeavour is essential for moving forward in our understanding of how the mind/brain processes words. To this aim, we encourage contributions exploring the relation between speech production and reading aloud. The questions the Research Topic should address include, but are not limited to, the following: To what extent are speech production and word reading/reading aloud similar? Are there some shared components and/or mechanisms between the two process? Is the time course of the (supposed) shared mechanisms activation similar in the two processes? How does the different input (conceptual vs. orthographic) interact with the types of information that reading and speaking share (semantic and phonological knowledge, articulatory codes)? How does a difference in the input affect the (supposed) common stages of processing (i.e., phonological encoding, and articulatory planning and execution)? We welcome any kind of contribution (e.g., original research article, review, opinion) that answers the above or other questions related to the Topic.